Metamaterials: How the subject started - Shamonina, E.; Solymar, L. (Metamaterials, 2007)
The circumstances leading to the birth of the subject of Metamaterials are analysed. The seminal papers, instrumental in establishing the initial momentum, are enumerated. A large number of closely related topics are described which contributed to the process of cross-fertilisation and led to sustained interest and further rapid development of this new subject.